Tingkat Maturasi dan Fertilisasi Oosit Domba yang Dimaturasi dalam Media dengan Imbuhan b-Mercaptoethanol Secara In Vitro (IN VITRO MATURATION AND FERTILIZATION RATE AT SHEEP OOCYTES MATURATED IN MEDIA WITH b-MERCAPTOETHANOL) - Bintara, Okky Adi; Setiadi, Mohamad Agus; Karja, Ni Wayan Kurniani (Jurnal Veteriner; Vol 16 No 4 (2015), 2016)
The objectives of this study to evaluate the effect of b-mercaptoethanol addition in maturation mediumon maturation and fertilization rate of sheep oocytes in vitro. Collected oocytes were then matured inmaturation medium without (control group) or with b-mercaptoethanol in concentration of 50 ?M or 100?M. There was a significant increase in the percentage of oocytes that reached the metaphase II (MII) stageafter cultured in maturation medium with b-mercaptoethanol either in concentration of 50 ?M or 100 ?M(p<0.05) (62.67%; 77.78%; 82.05% for control, 50 ?M, and 100 ?M group respectively). However no differencewas found in maturation rate of those oocytes in 50 ?M and 100 ?M groups (p>0.05). When maturedoocytes were fertilized, no difference was found on fertilization rate among the groups (P>0.05) (70.93%;77.50%; 69.14% for control, 50 ?M and 100 ?M group respectively). These data indicated that the additionof b-mercaptoethanol increased the percentage of sheep oocytes that reached the MII stage in vitro, but hadno effect on the fertilization rate.
Keywords: maturation; b-mercaptoethanol; fertilization; in vitro